Pengaruh Abu Kulit Durian sebagai Bahan Tambah dan Pengganti Sebagian Semen terhadap Kuat Tekan Beton K-175 - Muhammad Irvan Adi Wijayanto; Yudi Setio Prabowo (Institut Teknologi Garut, 2025)
Concrete is a primary material in construction that continues to be developed to improve efficiency and sustainability. One of the innovations pursued is the utilization of agricultural waste as an environmentally friendly additive in concrete mixtures. This study aims to examine the effect of adding and partially replacing Portland cement with durian peel ash on the compressive strength of K-175 grade concrete. The method employed was a laboratory experiment with variations of durian peel ash content of 0%, 0.3%, and 0.5%, incorporated into the concrete either as an additive or as a partial cement replacement. The test specimens were cube-shaped with dimensions of 15 × 15 × 15 cm, and compressive strength tests were conducted at the ages of 7 and 14 days. The results indicate that the addition of durian peel ash can increase the compressive strength of concrete, whereas partial replacement of cement with durian peel ash tends to reduce compressive strength. Nevertheless, the obtained compressive strength values remain below the standard requirement for K-175 concrete. These findings demonstrate the positive potential of durian peel ash as an environmentally friendly additive. Further research is recommended to optimize the mix composition and to examine the chemical characteristics of the ash in supporting pozzolanic reactions in concrete.